Asymmetry of deep medullary veins on susceptibility weighted MRI in patients with acute MCA stroke is associated with poor outcome - Mucke, Johanna; Möhlenbruch, Markus Alfred; Vollmuth, Philipp; Bäumer, Philipp; Gumbinger, Christoph; Purrucker, Jan; Mundiyanapurath, Sibu; Schlemmer, Heinz-Peter; Bendszus, Martin; Radbruch, Alexander (PLOS ONE, 2015)
Background and Purpose Due to its sensitivity to deoxyhemoglobin, susceptibility weighted imaging (SWI) enables the visualization of deep medullary veins (DMV) in patients with acute stroke, which are difficult to depict under physiological circumstances. This study assesses the asymmetric appearance of prominent DMV as an independent predictor for stroke severity and outcome. Materials and Methods SWI of 86 patients with acute middle cerebral artery (MCA) stroke were included. A scoring system from 0 (no visible DMV) to 3 (very prominent DMV) was applied for both hemispheres separately. A difference of scores between ipsi- and contralateral side was defined as asymmetric (AMV+). Occurrence of AMV+ was correlated with the National Institute of Health Stroke Scale (NIHSS) Score on admission and discharge, as well as the modified Rankin Scale (mRS) at discharge. Ordinal regression analysis was used to evaluate NIHSS and mRS as predictors of stroke severity, clinical course of disease and outcome. Results 55 patients displayed AMV+ while 31 did not show an asymmetry (AMV-). Median NIHSS on admission was 17 (11-21) in the AMV+ group and 9 (5-15) in the AMV- group (p = 0.001). On discharge median NIHSS was 11 (5-20) for AMV+ and 5 (2-14) for AMV- (p = 0.005). The median mRS at discharge was 4 (3-5) in the AMV+ group and 3 (1-4) in AMV- (p = 0.001). Odds ratio was 3.19 (95% CI: 1.24-8.21) for AMV+ to achieve a higher mRS than AMV- (p = 0.016). Conclusion The asymmetric appearance of DMV on SWI is a fast and easily evaluable parameter for the prediction of stroke severity and can be used as an additional imaging parameter in patients with acute MCA stroke.
Gesehen am 26.02.2018